Control over the preference for binding sites of polyoxometalates to silver ethynide clusters by surface charge modification. Issue 44 (8th October 2015) - Tamari, Sho; Ono, Kosuke; Hashimoto, Masato; Ozeki, Tomoji
Abstract : Site-specific substitution of Nb for W in an α-Keggin polyoxometalate leads to the formation of [Ag42 (CO3 )C}CC(CH3 )3 27 (α-A-SiW9 Nb3 O40 )2 ] −, where corner-shared triads of NbO6 octahedra bind to the Ag42 cluster moiety. Abstract : A polyoxometalate—silver ethynide composite cluster, [Ag42 (CO3 )C}CC(CH3 )3 27 (α-A-SiW9 Nb3 O40 )2 ] − (1 ), demonstrates that we can select the binding site of a polyoxometalate to the silver alkynide cluster by tuning the surface charge of the precursor polyoxometalate. Multidimensional and multinuclear NMR spectra revealed that1 maintains its precise atomic connectivity in the solution.